Atomistic and dynamic structural characterizations in low-dimensional materials: recent applications of in situ transmission electron microscopy. (18th November 2019) - Zheng, He; Cao, Fan; Zhao, Ligong; Jiang, Renhui; Zhao, Peili; Zhang, Ying; Wei, Yanjie; Meng, Shuang; Li, Kaixuan; Jia, Shuangfeng; Li, Luying; Wang, Jianbo
Abstract: In situ transmission electron microscopy has achieved remarkable advances for atomic-scale dynamic analysis in low-dimensional materials and become an indispensable tool in view of linking a material's microstructure to its properties and performance. Here, accompanied with some cutting-edge researches worldwide, we briefly review our recent progress in dynamic atomistic characterization of low-dimensional materials under external mechanical stress, thermal excitations and electrical field. The electron beam irradiation effects in metals and metal oxides are also discussed. We conclude by discussing the likely future developments in this area.